Urban Green Zones Planning Concept and Ecological Functionality (Through the Example of Poltava, Ukraine) - Smoliar, Natalia; Bredun, Viktor; Toronchenko, Olha (International Journal of Engineering and Technology, 2018)
In the article major peculiarities and problems in architectural and planning decisions concerning Poltava urban greening are represented, and ways of solving them are suggested. The townâ€™s green zones appropriation, their ecological, town-planning, sanitary and hygienic, recreational, and in case of some of them nature-sanctuary importance is considered. Structure and economical constituents of Poltava urban green zones planning, which represents average town urban ecosystemsÂ Â in the central (forest-steppe) zone of Ukraine, is analyzed. Maps and figures depicting typical schemes of manufacturing, transportation structure, density of population and urban greening are provided. Outraging of acceptable concentrations in dust and formaldehyde while analyzing urban atmospheric air pollution level according to the data obtained from stationary sites, is shown. These proves importance of taking into account consideration of interdependence between levels and locating of townâ€™s natural resources polluting sources, first of all atmospheric air, with urban territory greening planned decisions. Based on materials concerning study of green zones ecological functionality effectiveness peculiarities, the concept of Poltava urban green zones planning is suggested. Modern town architectural and planning decisions ecological aspects should be integrated into local strategies and development programs, town general lay-outs, transportation systems planning, strategy referring environmental protection, and require local self-government and state support.Â Â